IMPROVING STUDENTS’ SPEAKING SKILL USING DIGITAL PHOTOS THROUGH ONLINE LEARNING - Fasaaro Hulu (Asosiasi dosen IDEBAHASA KEPRI, 2021)
This research aimed at improving and developing the students’ speaking skill by using digital photos online. This research used zoom meeting aplication in online laerning toward the third grade of SMK Yos Anugrah Batam. The methode applied was a qualitatif research approach by descrining a picture, telling daily activities and telling experience. The research works conducted for three times in order to find out the improvement and the result of the participants. Each research works end, the partcipants were given test and questionaire to collect the real data by online. Data collected were analysed by scoring the students’ achievement for each activity based on the speaking ability criterion namely unfair, fair, good, very good and exellent. After the data scored through the test addressed to the students, researcher classified and grouped the data, organized and compared the data source, analyse the data, display and expalin the data in text according to the criterion speaking abilty. The result of this research was that the students’ speaking skill was improved and developed shown from the result.